Suppression of Botrytis cinerea, causative agent of gray mold of tomato by antagonistic bacteria - Badarunzaman, Nurul Huda (2018)
Botrytis cinerea is one of the most important fungal pathogen in tomato (Lycopersicon esculentum Mill.) worldwide. This fungal pathogen is also a major pathogen in other vegetables especially during postharvest stage. Botrytis cinerea, produces characteristic gray mold symptoms on fruits, leaves and stems within seven days following contamination. Thus, the objective of this study was to isolate and identify potential biocontrol agent (BCA) which have the ability to suppress growth of B. cinerea in-vitro. To achieve the objective, BCA was isolated from diseased and healthy tomato fruits. The botrytis cinerea was cultured in PDA medium and the bacteria was cultured in NA medium. The screening test was done via dual cultural test, culture filtrate test and spore suppression test. Finally, five potential BCA were identified in this test from bacteria isolate code BC4, BC23, BM4, BM11, and BM13 were found to be the most effective in suppressing growth of B. cinerea.